High speed pulsed laser cutting of LiCoO2 Li-ion battery electrodes. (1st September 2017) - Lutey, Adrian H.A.; Fortunato, Alessandro; Carmignato, Simone; Fiorini, Maurizio
Highlights: Li-ion battery electrodes are cut via pulsed laser irradiation at up to 5 m/s. Minimum average cutting power is obtained for 12 laser parameter groups at 1–5 m/s. Cutting efficiency and quality improve with higher repetition rate and velocity. At high velocity, clearance width is limited to areas directly exposed to the laser beam. Process parameters are realistic for immediate uptake of laser technology in industrial settings. Abstract: Laser cutting of Li-ion battery electrodes represents an alternative to mechanical blanking that avoids complications associated with tool wear and allows assembly of different cell geometries with a single device. In this study, laser cutting of LiCoO 2 Li-ion battery electrodes is performed at up to 5 m / s with a 1064 nm wavelength nanosecond pulsed fiber laser with a maximum average power of 500 W and a repetition rate of up to 2 MHz . Minimum average cutting power for cathode and anode multi-layer films is established for 12 parameter groups with velocities over the range 1 – 5 m / s, varying laser pulse fluence and overlap. Within the tested parameter range, minimum energy per unit cut length is found to decrease with increasing repetition rate and velocity. SEM analysis of the resulting cut edges reveals visible clearance widths in the range 20 – 50 μ m, with cut quality found to improve with velocity due to a reduction in lateral heat conduction losses. Raman line map spectra reveal changes in the cathode at 60 μ m from the cut edge, where bands at 486 cm - 1 and 595 cm - 1, corresponding to the E g and A 1 g modes of LiCoO 2, are replaced with a single wide band centered at 544 cm - 1, and evidence of carbon black is no longer present. No changes in Raman spectra are observed in the anode. The obtained results suggest that further improvements in cutting efficiency and quality could be achieved by increasing the repetition rate above 2 MHz, thereby improving ablation efficiency of the metallic conductor layers. The laser source utilized in the present study nonetheless represents an immediately available solution for repeatability and throughput that are superior to mechanical blanking.